PERENCANAAN AUDIT TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 (STUDI KASUS: PT. LAZ COAL MANDIRI) - Muh Wal Ikram; Winarno, Wing Wahyu; Arief, Muhammad Rudyanto (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
This study aims to identify and plan IT governance audits to support the business processes of PT. Laz Coal Mandiri. In achieving its goals, the company must synchronize the application of IT with the company's focus so that an information technology governance audit plan is needed at PT. Laz Coal Mandiri is aligned with the use of IT in companies. The purpose of an IT governance audit is to find out management discrepancies, optimize performance and to achieve the company's vision and mission. This research is supported by the absence of an assessment of the design of IT governance at the company. COBIT 2019 as the latest edition framework from ISACA makes improvements using design factors. The research method used is descriptive qualitative by conducting interviews with stakeholders. Obtained research results based on objective measurements of APO12 have a level of ability at level 2 while APO13 has a level of ability at level 1.